Urgensi Pengaturan Sanksi Pidana Terhadap Pelanggaran Nama Orang, Foto, dan Badan Hukum Terkenal Dalam Rezim Hukum Merek Di Indonesia - Amrulla, Moh. Fahrial (Esensi Hukum, 2025)
Law Number 20 of 2016 concerning Trademarks and Geographical Indications provides protection against the use of famous persons' names, photos, and legal entity names in trademark applications submitted to the Directorate General of Intellectual Property. Article 21 paragraph (2) letter a stipulates that a trademark application will be rejected if such elements are used without written consent from the rightful party. However, this provision only results in an administrative sanction rejection of the application without any accompanying criminal sanctions for violations. This normative gap reveals a significant weakness in the legal protection system for intellectual property in Indonesia. This study aims to analyze this legal void and provide recommendations for a more comprehensive legal framework, including the possibility of imposing criminal sanctions. The method used is normative juridical, involving analysis of legal statutes, legal literature, and comparative studies. The findings indicate that criminal sanctions are necessary to ensure deterrence and provide effective legal protection for owners of famous names and legal entities from acts that exploit or damage their reputation.